Development of the Positive Emotions Program for Schizophrenia: An Intervention to Improve Pleasure and Motivation in Schizophrenia - Nguyen, Alexandra; Frobert, Laurent; McCluskey, Iannis; Golay, Philippe; Bonsack, Charles; Favrod, Jérôme (Frontiers in Psychiatry, 2016)
Objectives: The efficacy of drug-based treatments and psychological interventions on the primary negative symptoms of schizophrenia remains limited. Recent literature has distinguished negative symptoms associated with a diminished capacity to experience, from those associated with a limited capacity for expression. The Positive Emotions Program for Schizophrenia (PEPS) is a new method that specifically aims to reduce the syndrome of a diminished capacity to experience. Methods: The intervention’s vital ingredients were identified through a literature review of emotion in schizophrenia and positive psychology. The program has been beta-tested on various groups of healthcare professionals. Results: A detailed description of the final version of PEPS is presented here. The French version of the program is freely downloadable. Conclusions: PEPS is a specific, short, easy to use, group-based intervention to improve pleasure and motivation in schizophrenia. It was built considering a recovery-oriented approach to schizophrenia.